On the anomalous development of a series of heavy rainfall events from central to north China during 19–21 July 2016. (23rd November 2021) - Xia, Rudi; Zhang, Da‐Lin; Fu, Shenming; Yin, Jinfang; Wang, Hongyan
Abstract: This study examines the development of a series of heavy rainfall events over four different geographical regions from central to north China on 19–21 July 2016, with the maximum 48‐hr‐accumulated and hourly rainfall amounts of 875 and 139 mm, respectively. Results show that the heavy rainfall events occurred in an environment with an anomalous deep trough associated with unusual extratropical cyclogenesis during this warm month and a pronounced moisture anomaly compared to a 30‐year climatology. The cyclogenesis coincided with dry‐air intrusion from the lower stratosphere, and its merging with a northwest and a southwest vortex in the lower troposphere, After its formation, the cyclone moved northward on the east side of Mt. Taihang and then northeastward across Mt. Yanshan. The presence of the southwest vortex and an abnormally strong western Pacific subtropical high contributed to the maintenance and intensification of a southwesterly low‐level jet (LLJ) carrying ample moisture, leading to the heavy rainfall in central China. The further enhanced southwesterly LLJ through the cyclogenesis and its accompanying southeasterly LLJ provided much needed precipitable water for the heavy rainfall events over north China. It was the quasi‐geostrophic forcing of the extratropical cyclone, together with its cold/warm frontal systems, and especially its northward movement with the approaching airflows near‐perpendicular to the general mountain orientations that provided optimized settings for the generation of a series of heavy rainfall events along the windward foothills of the major mountains in north China. Abstract : A series of four heavy rainfall events occurred across central and north China during 19–21 July 2016, with the maximum 48‐hr‐accumulated and hourly rainfall amounts of 875 and 139 mm, respectively. The presence of a southwest vortex and an abnormally strong western Pacific subtropical high contributed to the maintenance of a southwesterly low‐level jet carrying ample moisture, leading to the heavy rainfall in central China. It was the quasi‐geostrophic forcing of an extratropical cyclone, together with its frontal systems, and especially its northward movement with the approaching airflows near‐perpendicular to the general mountain orientations that provided optimized settings for the heavy rainfall in north China. Figure: Distribution of the 48 hr accumulated rainfall amount (shadings, mm) during 0200 BJT 19 to 0200 BJT 21 July 2016. Terrain heights are shaded in beige, starting from 500 m as contoured, with thick‐dashed lines denoting the major mountain ridges. Red rectangles denote the main heavy rainfall regions.